Solitary breast cancer metastasis to pelvic bone treated with a unique method of surgery combined with local doxorubicin administration - Bohatyrewicz, Andrzej; Karaczun, Maciej; Kotrych, Daniel; Ziętek, Paweł; Kołodziej, Łukasz; Jurewicz, Alina (Contemporary Oncology/Współczesna Onkologia, 2017)
Treatment of bone metastasis is a major challenge for current and future orthopedic and oncology specialists. For the treatment of single metastases, there is a continuing search for effective local treatments that do not affect the whole patient. The current report describes the case of single breast cancer metastasis to the pelvic bone in a 50-year-old woman treated surgically by bone osteotomy combined with local doxorubicin application. The presence of cancer cells was confirmed by histopathological examination. After 6 months, the same defect was operated on again and a successful therapeutic result was confirmed by negative tumor pathology tests. The bone defect caused by osteotomy was reconstructed with allogenic bone grafts that healed completely over 14 months. To the best of our knowledge, this report is the first to combine the removal bone metastasis with direct local cytostatic drug administration without the use of a specific carrier, followed by successful bone reconstruction 6 months later using bone allografts. Thus, single bone metastasis may be successfully treated with resection and local cytostatic administration, enabling bone reconstruction in the postoperative period. The potential benefits of such treatments must be evaluated by considering the potential risks involved, including necrosis of surrounding soft tissues and general reactions to the chemotherapy. No data has been available until now regarding the risk of cancer disease generalization being influenced by such treatments, but patient quality of life can be improved significantly by the successful removal of a solitary bone metastasis. The present case report supports the continuation of research on improving local cytostatic drug administration during the treatment of bone metastasis.